IMPORTANT ISSUES OF KNOWLEDGE OF FOREIGN LANGUAGES IN MODERN SOCIETY - Jumanazarova Asal; Tursunov Lochin Erkinovich (American Journals Publishing, 2023)
This article examines the role of a foreign language in modern society. Today, theoretical and practical aspects of the need and importance of learning and knowing foreign languages have been analyzed. The practical advantages of knowing and using foreign languages are also considered.
Keywords: the importance of learning a foreign language, modern personnel, language functions, the role of a foreign language, knowledge of foreign languages, professional necessity.